2010
DOI: 10.1016/j.jtbi.2010.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the effects of vasomotion on mass transport to tissue from axisymmetric blood vessels

Abstract: International audienceThe process known as vasomotion, rhythmic oscillations in vessel diameter, has been proposed to act as a protective mechanism for tissue under conditions of reduced perfusion, since it is frequently only observed experimentally when perfusion levels are reduced. This could be due to a resultant increase in oxygen transport from the vasculature to the surrounding tissue, either directly or indirectly. It is thus potentially of significant clinical interest as a warning signal for ischemia.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Mathematical modelling supports the importance of vasomotion for oxygen delivery (Ohta et al. 1988, Tsai & Intaglietta 1993, Goldman & Popel 2001, Pradhan & Chakravarthy 2007, Hapuarachchi et al. 2010) and suggests that its activity can change oxygen delivery to tissues by up to eightfold (Kislukhin 2010) although more recent analysis indicates a more complex role of vasomotion.…”
Section: Potential Consequences Of Vasomotionmentioning
confidence: 93%
See 1 more Smart Citation
“…Mathematical modelling supports the importance of vasomotion for oxygen delivery (Ohta et al. 1988, Tsai & Intaglietta 1993, Goldman & Popel 2001, Pradhan & Chakravarthy 2007, Hapuarachchi et al. 2010) and suggests that its activity can change oxygen delivery to tissues by up to eightfold (Kislukhin 2010) although more recent analysis indicates a more complex role of vasomotion.…”
Section: Potential Consequences Of Vasomotionmentioning
confidence: 93%
“…In one study (Goldman & Popel 2001), vasomotion only enhanced oxygen delivery in the skeletal muscle bed when myoglobin was low. In another modelling approach, where the physical movement of the arteriolar wall was included in the model, less oxygen delivery by the arterioles exhibiting vasomotion was found and it was suggested that this might lead to high oxygen tension and possibly enhanced delivery by the capillaries (Hapuarachchi et al. 2010).…”
Section: Potential Consequences Of Vasomotionmentioning
confidence: 99%
“…The blood perfusion has been demonstrated to be higher at acupoints and on certain parts of meridians [5,23]. Although the physiological role of microvascular vasomotion remains unclear, it has been shown to enhance blood ow and nutrient delivery [9,24]. The synchronous vasomotion suggested that the majority of skin microvessels at acupoints worked as a whole, which would release more energy than an irregular one.…”
Section: Discussionmentioning
confidence: 99%
“…5,20 Although the physiological role of microvascular vasomotion remains unclear, it has been shown to enhance blood flow and nutrient delivery. 6,21 The synchronous vasomotion suggested that the majority of skin microvessels at acupoints worked as a whole, which would release more energy than an irregular one. More energy and higher blood perfusion should be able to meet the needs of Qi and blood infusion.…”
Section: Discussionmentioning
confidence: 99%